Sympathetic innervation of the interscapular brown adipose tissue in mouse. Issue 1 (11th June 2019) - François, Marie; Torres, Hayden; Huesing, Clara; Zhang, Rui; Saurage, Carson; Lee, Nathan; Qualls‐Creekmore, Emily; Yu, Sangho; Morrison, Christopher D.; Burk, David; Berthoud, Hans Rudolf; Münzberg, Heike
Abstract: The recent discovery of significant brown fat depots in adult humans has revived discussion of exploiting brown fat thermogenesis in the control of energy balance and body weight. The sympathetic nervous system (SNS) has a key role in the activation of brown fat and functional mapping of its components will be crucial for the development of specific neuromodulation techniques. The mouse is an important species used for molecular genetic modulations, but its small size is not ideal for anatomical dissections, thus brown fat innervation studies are mostly available in larger rodents such as rats and hamsters. Here, we use pseudorabies virus retrograde tracing, whole tissue clearing, and confocal/light sheet microscopy to show the location of pre‐ and postganglionic neurons selectively innervating the interscapular brown adipose tissue (iBAT) in the mouse. Using iDISCO whole tissue clearing, we identified iBAT projecting postganglionic neurons in the caudal parts of the ipsilateral fused stellate/T1, as well as the T2−T5 sympathetic chain ganglia and preganglionic neurons between levels T2 and T6 of the ipsilateral spinal cord. The methodology enabled high‐resolution imaging and 3D rendering of the specific SNS innervation of iBAT and will be helpful to discern peripheral nervous system innervation of other organs and tissues. Abstract : Using iDISCO whole tissue clearing, we identified iBAT projecting postganglionic neurons in the caudal parts of the ipsilateral fused stellate/T1, as well as the T2−T5 sympathetic chain ganglia and preganglionic neurons between levels T2−T6 of the ipsilateral spinal cord. The methodology enabled high‐resolution imaging and 3D rendering of the specific SNS innervation of iBAT and will be helpful to discern peripheral nervous system innervation of other organs and tissues.